A FLORISTIC DESCRIPTION OF THE SAN PASTOR SAVANNA, BELIZE, CENTRAL AMERICA - Hicks, J.; Goodwin, Z. A.; Bridgewater, S. G. M.; Harris, D. J.; Furley, P. A. (Edinburgh Journal of Botany, 2011)
A vascular plant species list and description is provided for the San Pastor Savanna, an isolated area of savanna within the Chiquibul Forest Reserve, Belize. Of the 126 species recorded, 28 are new records for the Chiquibul Forest Reserve with one previously unrecorded for the country. The maintenance of the current vegetation classification under the Belize Ecosystems Map for the San Pastor Savanna is supported. The coarse-textured soils are typical for extremely seasonal climates with some evidence of prolonged inundation during wet periods and dry seasons affected by burning. Although clear floristic affinities exist with other local and regional savanna areas, the San Pastor Savanna has some unique features and its flora includes national endemics. Although it is currently protected as part of the Chiquibul Forest Reserve and this status should be maintained, its inaccessible location makes frequent monitoring by the Forest Department problematic. Through providing a source of water and a source of forage for horses, the San Pastor Savanna plays a pivotal role in supporting the illegal Chamaedorea (xaté) palm leaf harvesting industry. This activity has also adversely impacted local wildlife. Like the nearby Mountain Pine Ridge, the San Pastor Savanna has suffered intense pine beetle (Dendroctonus spp.) attack.
Keywords: Belize; floristics; phytogeography; Pinus caribaea; Pinus tecunumanii; savanna; wetlands